2018
DOI: 10.1017/ice.2017.267
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of ST395 KPC-Producing Klebsiella pneumoniae in a Neonatal Intensive Care Unit in Palermo, Italy

Abstract: Detection of staphylococcal cassette chromosome mec type XI carrying highly divergent mecA, mecI, mecR1, blaZ, and ccr genes in human clinical isolates of clonal complex 130 methicillin-resistant Staphylococcus aureus. Antimicrob Agent Chemother 2011;55:3765-3773. 5. Paterson GK, Larsen AR, Robb A, et al. The newly described mecA homologue, mecALGA251, is present in methicillinresistant Staphylococcus aureus isolates from a diverse range of host species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…ST307, ST395, ST392, ST348, ST405 and ST101) have been detected in our area. These results are consistent with the surveillance data from other authors [2024, 28]. Moreover, our findings on β-lactamase characterisation showed that the bla SHV gene was the most commonly found in our sample, followed by bla TEM and bla KPC, deviating from other studies [11, 29, 30], while respect to the KPC-type enzyme our results are in line with those of other studies - as the most commonly encountered is bla KPC-3 [21, 23, 3133].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…ST307, ST395, ST392, ST348, ST405 and ST101) have been detected in our area. These results are consistent with the surveillance data from other authors [2024, 28]. Moreover, our findings on β-lactamase characterisation showed that the bla SHV gene was the most commonly found in our sample, followed by bla TEM and bla KPC, deviating from other studies [11, 29, 30], while respect to the KPC-type enzyme our results are in line with those of other studies - as the most commonly encountered is bla KPC-3 [21, 23, 3133].…”
Section: Discussionsupporting
confidence: 94%
“…However, several reports have suggested an ongoing epidemiological change in the last years. In fact, whereas CC258 (ST258 and ST512) is still prevalent, several other STs are emerging and circulating [23, 24, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The bla KPC-41 -positive K. pneumoniae UM belonged to ST395, although the previously reported KPC producers exhibiting CZA resistance belonged to ST258 (6), ST307 (3), and ST1519 (11). It is noteworthy that an outbreak caused by a KPC-3-producing K. pneumoniae ST395 isolate (susceptibility to CZA not reported) has been reported in a neonatal intensive care unit in Palermo, Italy, and in our study the patient carrying K. pneumoniae UM also originated from Sicily (12).…”
mentioning
confidence: 42%
“…In one of our previous studies, 30 day fatality of infections with ST101 K.pneumoniae was found to be 72% (30). The ST395 clone is known as a potentially high-risk clone (32), and recent studies pointed out the emergence of carbapenem-resistant ST395 in France and Italy (33, 34). KPC-2 producing ST101 K. pneumoniae was shown to have the highest number of virulence genes associated with capsule type, attachment and iron uptake than the other epidemic clones of K.pneumonia (10).…”
Section: Discussionmentioning
confidence: 99%